Application of electrostatic force for the atomization improvement of urea-water sprays in diesel SCR systems. (15th February 2020) - Pratama, Raditya Hendra; Moon, Seoksu; Kim, Hyun-Ha; Oguma, Mitsuharu
Highlights: Electrostatic force effect on atomization of the urea-water solution was studied. Electrostatic spray structures were visualized by Mie-scattering technique. Microscopic spray characteristics were analyzed by a laser diffraction technique. Atomization and spray expansion of urea-water solution were enhanced by electrostatic force. Mechanism of the electrostatic force effect on urea-water spray atomization was discussed. Abstract: Urea-based selective-catalytic-reduction (SCR) system is one of the techniques applied to reduce NOx emission in diesel engines. Due to the application of low injection pressure to prevent the wall-wetting of the urea-water solution to the exhaust pipe, the spray atomization, which is important to increase the NOx conversion efficiency, is still unsatisfactory. In this study, we pay attention to the electrostatic force as a source to improve the spray atomization of the urea-water solution. An electric voltage up to 7 kV was charged to a single-hole nozzle injector and various injection pressures up to 7 MPa were applied to investigate how the effect of electric charge on spray atomization appears differently in different flow regimes. High-speed visualization was conducted to observe the macroscopic spray structure. The microscopic spray characteristics were analyzed by a laser diffraction technique. The results showed that the electrostatic force effect, which results in finer droplet size and wider spray coverage area, is obtained especially at higher applied voltage in two different manners depending on the injection pressure, i.e. electrostatic induced jet breakup as a dominant effect at low injection pressures and electrostatic repulsion force-induced spray expansion as a dominant effect at high injection pressures.